Fragment-based design of selective GPCR ligands guided by free energy simulations. Issue 92 (4th November 2021) - Matricon, Pierre; Vo, Duc Duy; Gao, Zhan-Guo; Kihlberg, Jan; Jacobson, Kenneth A.; Carlsson, Jens
Abstract : Fragment-based drug discovery relies on successful optimization of weakly binding ligands for affinity and selectivity. Abstract : Fragment-based drug discovery relies on successful optimization of weakly binding ligands for affinity and selectivity. Herein, we explored strategies for structure-based evolution of fragments binding to a G protein-coupled receptor. Molecular dynamics simulations combined with rigorous free energy calculations guided synthesis of nanomolar ligands with up to >1000-fold improvements of binding affinity and close to 40-fold subtype selectivity.